2018
DOI: 10.1161/jaha.118.009145
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Outcome From Prenatal Diagnosis Through Fontan Operation for Over 500 Fetuses With Single Ventricle‐Type Congenital Heart Disease: The Philadelphia Fetus‐to‐Fontan Cohort Study

Abstract: Background Prenatal diagnosis of single ventricle‐type congenital heart disease is associated with improved clinical courses. Prenatal counseling allows for optimal delivery preparations and opportunity for prenatal intervention. Expectant parents frequently ask what the likelihood of survival through staged palliation is and the factors that influence outcome. Our goal was specifically to quantify peri‐ and postnatal outcomes in this population. Methods and Results We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…5,6,8,9 The overall low utilisation of cardiac care in the live-born babies in this study is different from reports from the developed world where the majority receive specialised cardiac care. 21,22 This is despite the fact that all palliative surgeries for univentricular heart were being performed in our centre from the inception of the study. A recent report had highlighted the feasibility of single ventricle palliations in the setting of low-and-middle-income countries with encouraging early outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,8,9 The overall low utilisation of cardiac care in the live-born babies in this study is different from reports from the developed world where the majority receive specialised cardiac care. 21,22 This is despite the fact that all palliative surgeries for univentricular heart were being performed in our centre from the inception of the study. A recent report had highlighted the feasibility of single ventricle palliations in the setting of low-and-middle-income countries with encouraging early outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7 We observed that intention-to-treat and cardiac procedures were more common in patients with systemic left ventricle, which has been shown to be associated with better long-term Fontan outcomes. 21,22 The medical costs of the staged single ventricle palliation pathway will consume about 5 times the average per capita annual income of a family in Kerala. 31 In addition, the annual clinic visits, evaluation and medications will exceed an average monthly income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] The HLHS diagnosis constituted close to a third of the cases included in our analysis. Even though at least 67% of prenatally diagnosed HLHS survive transplant-free to at least 6 months beyond the Fontan operation, which is the last surgical step in the single ventricle pathway approach to postnatal HLHS management, 22 in our cohort we included women with diagnosis of fetal HLHS who chose to pursue palliative care at birth. Therefore, in this analysis, they were considered as having a fetal life-limiting condition.…”
Section: Discussionmentioning
confidence: 99%
“…BMCs have been studied extensively and are known to be safe in several scenarios of bone marrow reconstitution in ischemic HF of the adult. The unique possibility to yield high numbers of CDC in patients operated for CHD in the neonatal period and myocardial repopulation during a planned surgery at an early phase of myocardial dysfunction in infancy might be preventive for the known deterioration process in univentricular hearts (34,35).…”
Section: Cell Types Applied For Cardiac Regeneration In Childrenmentioning
confidence: 99%